Analisis Penggunaan Sistem Informasi Akuntansi Dalam Meningkatkan Efisiensi Pengelolaan Zakat Di Baznas Provinsi Jawa Barat - Siti Nur Azizah; Gina Sakinah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Effective and efficient zakat management is essential to achieving social welfare and economic equity in society. The National Amil Zakat Agency (BAZNAS), as the official zakat management institution in Indonesia, needs to implement a transparent and accountable system in every operational process. This study aims to analyze the use of Accounting Information Systems in improving the efficiency of zakat management at BAZNAS West Java Province. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the BAZNAS Management Information System (SIMBA), as a form of Accounting Information Systems, plays a crucial role in enhancing the efficiency and transparency of zakat management, particularly in recording, reporting, and monitoring zakat funds. Although there are challenges such as discrepancies in certain chart of accounts between the central and regional BAZNAS, the system generally improves the accuracy of financial data and speeds up the reporting process. Therefore, the use of AIS through SIMBA is considered effective in supporting professional, efficient, and accountable zakat governance at BAZNAS West Java Province.